The muon beam monitor for the FAMU experiment: design, simulation, test, and operation - Rossini, R.; Baldazzi, G.; Banfi, S.; Baruzzo, M.; Benocci, R.; Bertoni, R.; Bonesini, M.; Carsi, S.; Cirrincione, D.; Clemenza, M.; Colace, L.; De Bari, A.; et al. (Frontiers in Detector Science and Technology, 2024)
FAMU is an INFN-led muonic atom physics experiment based at the RIKEN-RAL muon facility at the ISIS Neutron and Muon Source (United Kingdom). The aim of FAMU is to measure the hyperfine splitting in muonic hydrogen to determine the value of the proton Zemach radius with accuracy better than 1%. The experiment has a scintillating-fibre hodoscope for beam monitoring and data normalisation. In order to carry out muon flux estimation, low-rate measurements were performed to extract the single-muon average deposited charge. Then, detector simulation in Geant4 and FLUKA allowed a thorough understanding of the single-muon response function, crucial for determining the muon flux. This work presents the design features of the FAMU beam monitor, along with the simulation and absolute calibration measurements in order to enable flux determination and enable data normalisation.